Absorption, Distribution, Metabolism, and Excretion (ADME) Studies of Biotherapeutics for Autoimmune and Inflammatory Conditions - Vugmeyster, Yulia (Springer US, 2012)
Biotherapeutics are becoming an increasingly common drug class used to treat autoimmune and other inflammatory conditions. Optimization of absorption, distribution, metabolism, and excretion (ADME) profiles of biotherapeutics is crucial for clinical, as well as commercial, success of these drugs. This review focuses on the common questions and challenges in ADME optimization of biotherapeutics for inflammatory conditions. For these immunomodulatory and/or immunosuppressive biotherapeutics, special consideration should be given to the assessment of the interdependency of ADME profiles, pharmacokinetic/pharmacodynamic (PK/PD) relationships, and immunogenicity profiles across various preclinical species and humans, including the interdependencies both in biology and in assay readouts. The context of usage, such as dosing regimens, extent of disease, concomitant medications, and drug product characteristics may have a direct or indirect (via modulation of immunogenicity) impact on ADME profiles of biotherapeutics. Along these lines, emerging topics include assessments of preexisting reactivity to a biotherapeutic agent, impact of immunogenicity on tissue exposure, and analysis of penetration to normal versus inflamed tissues. Because of the above complexities and interdependences, it is essential to interpret PK, PD, and anti-drug antibody results in an integrated manner. In addition, because of the competitive landscape in autoimmune and inflammatory markets, many pioneering ADME-centric protein engineering and subsequent in vivo testing (such as optimization of novel modalities to extend serum and tissue exposures and to improve bioavailability) are being conducted with biotherapeutics in this therapeutic area. However, the ultimate challenge is demonstration of the clinical relevance (or lack thereof) of modified ADME and immunogenicity profiles.